2002
DOI: 10.1039/b204657a
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of the reaction between atomic chlorine and dimethyl selenide; comparison with the reaction between atomic chlorine and dimethyl sulfide

Abstract: Dimethyl selenide is the most abundant gaseous selenium species in marine environments. In this work, the value of the rate coefficient for the gas-phase reaction between dimethyl selenide and Cl atoms has been determined for the first time. The value of the second-order rate coefficient obtained was (5.0 ± 1.4) × 10 −10 cm 3 molecule −1 s −1 . The very fast nature of the reaction means that, when estimating the lifetime of dimethyl selenide in the atmosphere, loss due to reaction with Cl atoms should be consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 38 publications
(118 reference statements)
1
17
0
Order By: Relevance
“…The most recent value of 17.7 kcal mol -1 , reported by Enami et al, at the QCISD(T)/MP/6-311++G(2df.2p) level lies between the previous determinations. Thompson et al reported values of Δ r H ° for formation of the (CH 3 ) 2 S−Cl adduct which are in good agreement with the value of Wilson and Hirst 167 but not with the calculated values of by McKee 106 or Resende and De Almeida …”
Section: 32 Products and Mechanism Of The CL + Dms Reactionmentioning
confidence: 82%
“…The most recent value of 17.7 kcal mol -1 , reported by Enami et al, at the QCISD(T)/MP/6-311++G(2df.2p) level lies between the previous determinations. Thompson et al reported values of Δ r H ° for formation of the (CH 3 ) 2 S−Cl adduct which are in good agreement with the value of Wilson and Hirst 167 but not with the calculated values of by McKee 106 or Resende and De Almeida …”
Section: 32 Products and Mechanism Of The CL + Dms Reactionmentioning
confidence: 82%
“…It is also interesting to compare the reaction of DMSe with atomic and molecular chlorine, as both reactions involve the formation of a covalent intermediate: DMSeCl and DMSeCl 2 . The DMSeCl intermediate forms on addition of Cl to the Se atom . The Se–Cl bond is longer in DMSeCl (2.73 Å at the B3LYP/6-311++G(d,p)level) than in DMSeCl 2 (2.562 Å, this work), while the C–Se–C bond angle is smaller in DMSeCl (98.1° at the B3LYP/6-311++G(d,p) level) than in DMSeCl 2 (98.5°, this work).…”
Section: Resultsmentioning
confidence: 61%
“…The DMSeCl intermediate forms on addition of Cl to the Se atom . The Se–Cl bond is longer in DMSeCl (2.73 Å at the B3LYP/6-311++G(d,p)level) than in DMSeCl 2 (2.562 Å, this work), while the C–Se–C bond angle is smaller in DMSeCl (98.1° at the B3LYP/6-311++G(d,p) level) than in DMSeCl 2 (98.5°, this work). The same trends are observed on comparing the structures of the covalent intermediates of DMS with atomic and molecular chlorine computed at the UMP2/DZP and MP2/aug-cc-PVDZ levels, respectively. , …”
Section: Resultsmentioning
confidence: 61%
“…Langer et al [768] coupled cw photolysis with gas chromatographic detection of products to show that the yield of CH 3 Cl is (1.34 ± 0.07) x 10 . Theoretical studies by Wilson and Hirst [1459], Resende and De Almeida [1114] and Thompson et al [1299] support the experimentally-observed dominance of the H-abstraction pathway at low pressure. Diaz-de-Mera et al [390] have employed a discharge flow − mass spectrometry technique to measure rate constants at pressures of 0.5 − 1.0 Torr He over the temperature range 259 − 364 K. The 298 K rate constant reported by Diaz-de-Mera et al is nearly a factor of 3 slower than the low-temperature limit value reported by Stickel et al Furthermore, Diazde-Mera et al report a small positive activation energy whereas Stickel et al report a small negative activation energy.…”
Section: -104mentioning
confidence: 58%